Soil aggregation and aggregate associated organic carbon and total nitrogen under long-term contrasting soil management regimes in loess soil - Jun-yu XIE; Ming-gang XU; Qiangjiu Ciren; Yang YANG; Shu-lan ZHANG; Ben-hua SUN; Xue-yun YANG (Journal of Integrative Agriculture)
This study investigated the effects of three contrasting soil management regimes and different nutrient treatments on the distribution of water-stable aggregates (>2, 1–2, 0.5–1, 0.25–0.5, and <0.25 mm) and associated soil organic carbon (SOC) and total nitrogen (TN) content in loess soil. A 21-yr long-term experiment was performed, in which soil management regimes include cropland abandonment (Abandonment), bare fallow (Fallow) and wheat-fallow cropping (Cropping). Under Cropping, the following nutrient treatments were employed: control (CK, no nutrient input), nitrogen only (N), nitrogen and potassium (NK), phosphorus and potassium (PK), NP, NPK, and manure (M) plus NPK (MNPK). Results demonstrated that Abandonment significantly increased the content of soil macro-aggregates (>0.25 mm) and mean weight diameter (MWD) at 0–10 and 10–20 cm soil horizons compared with Cropping, whereas Fallow yielded lower values of above two parameters. Abandonment increased SOC and TN contents in all aggregate sizes by 17–62% and 6–60%, respectively, at 0–10 cm soil layer compared with Cropping. Conversely, Fallow decreased SOC and TN contents in all aggregates by 7–27% and 7–25%, respectively. Nevertheless, the three soil management regimes presented similar SOC contents in all aggregates at 10–20 cm soil horizon. Only Cropping showed higher TN content in >0.5 mm aggregates than the two other regimes. Consequently, Abandonment enhanced the partitioning proportions of SOC and TN in >1 mm macro-aggregates, and Fallow promoted these proportions in micro-aggregates compared with Cropping. Under Cropping, long-term fertilization did not affect the distribution of aggregates and MWD values compared with those under CK, except for NPK treatment. Fertilizer treatments enhanced SOC and TN contents in aggregates at all tested soil depths. However, fertilization did not affect the partitioning proportions of SOC and TN contents in all aggregates compared with CK. Comprehensive results showed that different soil management regimes generated varied patterns of SOC and TN sequestration in loess soil. Abandonment enhanced soil aggregation and sequestered high amounts of SOC and TN in macro-aggregates. Long-term amendment of organic manure integrated with NPK maintained soil aggregate stability and improved SOC and TN sequestration in all aggregates in loess soil subjected to dryland farming.